a.\(4FeS_2+11O_2\rightarrow\left(t^o\right)2Fe_2O_3+8SO_2\)
\(2SO_2+O_2\rightarrow\left(t^o,V_2O_5\right)SO_3\)
\(SO_3+H_2O\rightarrow H_2SO_4\)
\(Fe_2O_3+3H_2SO_4\rightarrow\left(t^o\right)Fe_2\left(SO_4\right)_3+3H_2O\)
c.\(Fe_2O_3+3H_2\rightarrow\left(t^o\right)2Fe+3H_2O\)
b.\(Fe+H_2SO_4\rightarrow FeSO_4+H_2\)
LẤY FeS td với H2O
2FeS2 + 19H2O → Fe2O3 + 15H2 + 4H2SO4
lấy Fe2O3 td với H2SO4
Fe2O3 + 3H2SO4 -> Fe2(SO4)3 + 3H2
ta lấy H2 khử Fe2O3
Fe2O3 + 3H2 -t-> 2Fe + 3O2
lấy Fe td vỡi Fe2(SO4)3
Fe+Fe2(SO4)3 -> 3FeSO4